The genus Nassella (Poaceae: Stipeae) in Mexico - Valdes Reyna, Jesus; E. Barkworth, Mary (Instituto de Ecología, A.C., 1994)
Nassella Desvaux is a genus of the grass tribe Stipeae. It was originally described for Central and South American species, and generally was interpreted as consisting of plants with short florets, blunt calluses, non-striate lemmas with overlapping margins and readily deciduous awns. Pohl (1980), Barkworth and Everett (1987) and Barkworth (1990) adopted a much broader interpretation of Nassella, one that would include many species traditionally placed in Stipa. Under this interpretation in Mexico exist eight species of Nassella, which are widely distributed in the country. In this paper the evidence supporting this expansion of Nassella is reviewed. Keys to genera and species are presented as well as a distribution map for its Mexican members.